A novel eddy current damper system for multi-mode high-order vibration control of ultra-long stay cables. (1st July 2022) - Wang, Yafei; Chen, Zhengqing; Yang, Chao; Liu, Zhiwen; He, Jia; Feng, Zhouquan
Highlight: The wind-induced vibrations of stay cables can be classified into RWIV, VIV and micro-vibration. A novel eddy current dampers system is developed to suppress the multi-mode high-order vibration of the ultra-long stay cables. A new damping coefficient design method for the dampers is proposed, which is verified by lab and field forced vibration tests. The practical wind-induced vibration control effects of the proposed damper system are verified by field measurement data. Abstract: Recently, the multi-mode high-order wind-induced vibration of the ultra-long stay cables has been observed on several cable-stayed bridges, which may result in a visual panic of the users and the fatigue of the stay cables at anchorage ends. In order to investigate the multi-mode high-order wind-induced vibration characteristics of ultra-long stay cables, a vibration monitoring system (VMS) of the stay cables is established on the Sutong Bridge (STB). Furthermore, to suppress the in-plane and out-of-plane vibration responses of the stay cables simultaneously, a novel eddy current damper system (ECDS) is proposed in this study. The damping coefficients of the ECDS for multi-mode high-order vibration of the stay cables are determined via a modified method. Moreover, laboratory tests are conducted to evaluate the performance of the developed dampers. Furthermore, the field tests of seven stay cables of the STB are carried out to identify the modal damping ratios of the cable-damper system via the free vibration method. The results show that it is feasible to provide sufficient additional modal damping ratios for multi-mode high-order vibration of ultra-long stay cables applying the ECDS proposed in this study. Finally, the one-year field measurements of the wind-induced vibration responses of the seven stay cables of the STB are carried out to validate the ECDS suppress effects on multi-mode high-order vibration control of ultra-long stay cables. The measurement results show that the multi-mode high-order vibration responses of the monitored stay cables of the STB are effectively suppressed.